2020
DOI: 10.14309/ctg.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Is Peer Support in Group Clinics as Effective as Traditional Individual Appointments? The First Study in Patients With Celiac Disease

Abstract: INTRODUCTION: Celiac disease (CD) is common, affecting approximately 1% of the population. The cornerstone of management is a gluten-free diet, with dietetic advice being the key to aiding implementation. The aim of the study was to assess group clinics in comparison with traditional individual appointments. METHODS: Patients with a new diagnosis of CD, confirmed histologically, were prospectively recruited over 18 months in Sheffield, United Kingdom. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Moreover, in the group-based education, the patients find more other patients with similar concerns, and their anxiety level about the disease was decreased and they become more motivated to increase their adherence to GFD, and consequently their quality of life improve [ 29 , 35 , 36 ]. However, Rej et al, showed that group-based education of newly diagnosed patients with CD has no significant effect on QOL [ 25 ]. The discrepancy between the results of the present study and Rej et al study partly can be attributed to the characteristics of included participants since they included the newly diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the group-based education, the patients find more other patients with similar concerns, and their anxiety level about the disease was decreased and they become more motivated to increase their adherence to GFD, and consequently their quality of life improve [ 29 , 35 , 36 ]. However, Rej et al, showed that group-based education of newly diagnosed patients with CD has no significant effect on QOL [ 25 ]. The discrepancy between the results of the present study and Rej et al study partly can be attributed to the characteristics of included participants since they included the newly diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobbson et al reported that celiac school improves psychological health and gastrointestinal (GI) symptoms in patients with CD [ 24 ]. Rej et al also reported that in patients with newly diagnosed CD, group clinics had a positive effect on patients' QOL [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietetic services in the UK have been demonstrated to be inadequately resourced, with the majority of trusts not providing specialist clinics, 37 and thus innovative methods for providing dietetic services are required such as group clinics, 38 telephone clinics or digital apps. If a pathway could be created that is achievable and economical for the whole of the UK then this system could be mandated by the Coeliac National Charity perhaps under the auspices of a patient charter.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have investigated the association between CeD and the social domain of QOL [13][14][15][16]. A study investigating the efficacy of one-on-one counseling versus group counseling sessions found higher anxiety scores in the group-counseled participants compared to the one-on-one category.…”
Section: Introductionmentioning
confidence: 99%